Employee Voice Behavior of Governmental Organization - Godefridus Yulian Garung; Tri Siwi Agustina; Anis Eliyana; Yeni Fajariyanti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Previous research has tested the effect of cultural intelligence on voice behaviour by using transformational leadership as a mediating variable. This study presents a different perspective using the ethical leadership variable as a mediation. This study examines the effect of cultural intelligence on voice behaviour with ethical leadership as a mediating variable. Research data were collected from 492 employees of the Ministry of Justice and Human Rights of the Republic of Indonesia. The results showed that cultural intelligence significantly affected employee voice behaviour and ethical leadership, mediating cultural intelligence and employee voice behaviour. This research can be used as a reference for application in multicultural organizations, especially in voice behaviour.